Nafas studio / Alya Farah Nadya Rosli … [et.al.]. - Rosli, Alya Farah Nadya; Ali, Azah; Abdul Rani, Farhani; Daud, Nur Nabihah; Joblee, Saiyyidah Nafisah (2014)
Our company name is NAFAS Studio. The business has been decided in the form of partnership. Each of us has contribution certain amount of capital as agreed in our agreement. Our main business activity is to provide handicraft style which is nearby to the. We will provide our shop at Level 2, Lot 5358 Fasa 25, Jalan Datuk Mohd Musa, Taman Desa Ilmu, Sarawak, 94300 Kota Samarahan and our business will be commence by 1st January 2014.All five of us have agreed to participate in all business management that we will establish that is Alya Farah Nadya binti Rosli as General Manager, Azah binti Ali as Marketing Manager, Farhani binti Abdul Rani as Financal Manager, Nurnabihah Daud as Operation Manager and Sayyidah Nafisah bt Joblee as Administration Manager.